Wewenang Penggunaan Aset Desa Dalam Bentuk Rumah Kepala Desa Oleh Mantan Kepala Desa - Sanabuky, Kristo; Nirahua, Salmon Eliazer Marten; Bakarbessy, Andress Deny (CAPITAN: Constitutional Law & Administrative Law Review, 2023)
The Village Head holds the power to carry out the management of finances and Village Assets which of course must be based on laws and regulations and applicable legal principles. However, inreality, the management of Village Assets is not carried out in accordance with applicable legal principles, so that Village Assets are used personally by the Former Village Head, in Keliobar Village, North Tanimbar District, Tanimbar Islands Regency. Based on this problem, it is important to examine the authority to use Village Assets in the form of a Village Head's house. The legal issue is whether the former village head is authorized to use village assets in the form of village head houses, and whether the legal consequences for the use of village assets in the form of village head houses. The purpose of this study is to determine the authority to use village assets in the form of Village Head Houses by former Village Heads, and to find out the legal consequences on the use of Village Assets in the Form of Village Heads' Houses. This study uses a normative legal research method using a statutory approach and a conceptual approach. The results and discussion show that: 1). The former Village Head is not authorized to use Village Assets in the form of a Village Head's House based on the provisions of article 10 Paragraph (1) of the Minister of Home Affairs Regulation number 1 of 2016 concerning Village Asset Management, and 2). There is a change in the status of the use of Village Assets which results in losses to state finances so that the person concerned or the user, can be subject to administrative fines.